An Energy Level Alignment Study of 2PACz Molecule on Perovskite Device‐Related Interfaces by Vacuum Deposition - Jielei Li; Shengwen Li; Bingchen He; Ruifeng Zheng; Yulin Wang; Shi Chen (Advanced Energy & Sustainability Research)
Self‐assembling molecules (SAM) have been widely used in inverted perovskite solar cells (PSC) as a hole transfer layer due to nearly lossless charge transfer giving excellent device performance. However, the energy level alignment between SAM‐ and PSC‐related interfaces has not been systematically studied. Herein, the 2PACz, a typical SAM with the largest dipole moment, is chosen as the model system and is studied by vacuum deposition. It is found that the energy level alignment is determined by the orientation of 2PACz molecules on a different substrate. The molecules are lying down on highly oriented pyrolytic graphite and giving nearly zero interface dipole. On solvent‐cleaned and plasma‐treated indium tin oxide (ITO) substrates, the SAM is vertically assembled with 0.22 and 0.13 eV work function increases, respectively. However, on sputtered ITO, SAM is assembled with upside down orientation, with 0.51 eV work function decrease. The change of orientation is due to strong interaction between oxygen vacancies in ITO substrate and carbazole head group of 2PACz. On perovskite film, SAM also shows a slightly upward orientation with additional passivation of free MA+ ions. Herein, it is confirmed that the energy level alignment of SAM plays an important role in hole extraction.